INVESTIGATION OF STATE/TRAIT ANXIETY SITUATION OF NURSES WORKING IN PSYCHIATRY CLINICS - Aslanoğlu, Eren (Mus Alparslan University, 2023)
In our study, it was aimed to determine the anxiety levels and levels associated with nurses working in psychiatry inpatient services and related factors. Our study, which is a cross-sectional study, was carried out on 177 nurses working in Elazig Mental Health Hospital. In the study, no sample selection was made, and all nurses participated in the study. To the nurses within the scope of the study; The questionnaires included in the State-Trait Anxiety Inventory were applied, along with the socio-demographic characteristics and health and social questions that are thought to affect the anxiety level. In the analysis of the study data, t test, mean, percentile and Kruskal-Wallis tests were applied. In the study, it was understood that 59.9% of the nurses were female, 59.9% had a bachelor's degree, and 74% were married, and their total scores were calculated as 41.00±9.42 on the State Anxiety Inventory and 41.00±7.89 on the Trait Anxiety Inventory. In the study, when the nurses' perceptions of their economic situation were compared with the total score averages from the state-trait anxiety scale, the difference was evaluated as significant (p

Çalışmamızda, psikiyatri yataklı servislerinde görev yapan hemşirelerin yaşayabilecekleri kaygıları ve düzeylerini bununla birlikte ilişkili faktörleri saptayabilmek amaçlanmıştır. Kesitsel tipte bir araştırma olan çalışmamız, Elazığ Ruh Sağlığı Hastalıkları Hastanesinde fiili görev alan 177 hemşireye yapılmıştır. Çalışmada örneklem seçimine gidilmeyerek tüm hemşirelerin çalışmaya katılımı sağlanmıştır. Çalışma kapsamına hemşirelere; sosyo-demografik özellikler ve kaygı düzeyini etkileyebileceği düşünülen sağlık ve sosyal içerikli sorular ile birlikte Durumluk-Sürekli Kaygı Envanteri’nde yer alan anketler uygulanmıştır. Çalışma verilerinin analizinde t testi, ortalama, yüzdelik ve Kruskal-Wallis testleri uygulanmıştır. Çalışmada hemşirelerin %59.9’unun kadın, %59.9’unun lisans mezunu, %74 ünün evli olduğu anlaşılmış, Durumluk Kaygı Ölçeği 41.00±9.42 olarak Sürekli Kaygı Ölçeği ise 41.00±7.89 olarak toplam puanları hesaplanmıştır. Çalışmada, hemşirelerin ekonomik durumlarını algılamalarıyla durumluk-sürekli kaygı ölçeğinden ortaya çıkan toplam puan ortalamaları kıyaslandığında ortaya çıkan fark anlamlı olarak değerlendirilmiştir (p
PSİKİYATRİ KLİNİKLERİNDE ÇALIŞAN HEMŞİRELERİN DURUMLUK-SÜREKLİ KAYGI DURUMUNUN İNCELENMESİ
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi